Rushed health workforce reform in South Korea: a Kingdon’s multiple streams framework analysis of the 2024 medical school quota expansion - Lee, Yuri; Shin, Hyun-Young (Frontiers in Public Health, 2025)
BackgroundIn 2024, South Korea expanded medical school quotas to address physician shortages in underserved regions and essential specialties. Public concerns emerged over equity and distribution amid political pressure, limited stakeholder participation, and opaque workforce forecasts.ObjectiveTo explain how political dynamics, stakeholder exclusion, and weak integration of evidence shaped rapid policy change, and to assess implications for workforce planning and essential-care access.MethodsWe conducted a mixed-methods policy analysis using qualitative data from policy documents, legislative records, and media coverage, alongside secondary quantitative data on physician distribution and residency application trends. Thematic coding and triangulation were guided by the three streams of Kingdon’s multiple streams framework: problem, policy, and politics.ResultsThe findings reveal that policy urgency was driven by focusing events such as maternal emergencies and pediatric access crises. While numeric expansion was politically favored, workforce projections were inconsistent and failed to address specialty-specific and regional gaps. Political actors prioritized electoral considerations over evidence-based, inclusive reform strategies.ConclusionQuota expansion alone is unlikely to resolve disparities. Sustainable reform requires transparent forecasting, targeted incentives, capacity for priority specialties/regions, and participatory governance with multi-stakeholder collaboration.